Cerebrospinal Fluid Inflammatory Cytokine Levels in Patients With Major Psychiatric Disorders: A Multiplex Immunoassay Study - Hidese, Shinsuke; Hattori, Kotaro; Sasayama, Daimei; Tsumagari, Takuya; Miyakawa, Tomoko; Matsumura, Ryo; Yokota, Yuuki; Ishida, Ikki; Matsuo, Junko; Yoshida, Sumiko; Ota, Miho; Kunugi, Hiroshi (Frontiers in Pharmacology, 2021)
Aim: Accumulating evidence suggests that neural inflammation plays an important role in psychiatric disorders. We aimed to identify inflammatory cytokines involved in the pathophysiology of such disorders by quantifying them in cerebrospinal fluid (CSF) samples from a large sample of patients with major psychiatric disorders and healthy controls. Methods: The subjects included 94 patients with schizophrenia, 68 with bipolar disorder, 104 with major depressive disorder, and 118 healthy controls, matched for age, sex, and ethnicity (Japanese). Lumbar puncture was performed to collect these CSF samples. A multiplex immunoassay was then performed to measure CSF cytokine levels using magnetic on-bead antibody conjugation for 19 inflammatory cytokines. Results: CSF interferon-β levels were significantly higher in total psychiatric patients than in healthy controls (corrected p = 0.000029). CSF interferon-β level was significantly higher in patients with schizophrenia, or bipolar disorder (corrected p = 0.000047 or 0.0034) than in healthy controls. Conclusion: We present novel evidence that CSF IFN-β level showed prominent statistical differences between psychiatric groups and healthy controls. This suggests IFN-β as the most important player among the 19 cytokines tested here in the inflammation-related pathophysiology of major psychiatric disorders.